Plant-based diets–impacts of consumption of little or no animal-source foods on human health - Stanton, Alice V. (Frontiers in Nutrition, 2024)
The world, in 2024, faces both climate and biodiversity crises, and the food system does contribute significantly to these crises. For some, the solution is simple -intakes of animal source foods (ASFs) should be considerably reduced, and consumption of plant-source foods (PSFs) should be greatly increased. Advocates for such a dietary transformation express confidence that plant-based diets will not only benefit planetary health, but will provide nutrient adequacy for all, and will also result in considerable protection from chronic non-communicable diseases (NCDs).However, as described in this perspective, the dramatic reductions in ASFs, entailed by many plantbased diets, will worsen already prevalent micronutrient and protein deficiencies. The protections provided by plant-based diets against NCDs appear to be more strongly associated with reduced intakes of calories and salt, and increased intakes of fruit, vegetables, nuts and whole grains, rather than with reduced intakes of ASFs. Any possible absolute adverse effects of red and processed meat consumption on NCDs are very small and uncertain. Other ASFs either appear to have no impact on NCDs (poultry meat and eggs), or are associated with protections against obesity, cardiovascular events, brain disorders and some cancers (seafood and dairy).Rigorous randomised controlled trials of all newly proposed environmentally-protective plant-based diets are required, so as to provide clear-cut evidence of micronutrient and protein adequacy, with or without, supplementation, fortification and/or biofortification. In the meantime, dietary guidelines should advise moderating excessive consumption, rather than substantially limiting or excluding ASFs from the human diet.